A study on teaching listening comprehension to the 10th form students at Ly Thuong Kiet High School - Bac Giang = Nghiên cứu về việc dạy kĩ năng nghe hiểu cho học sinh lớp 10 trường THPT Lý Thường Kiệt - Bắc Giang. M.A. Thesis Linguistics: 60 14 10 - Phạm, Thị Yến (ĐHNN, 2017)
40 p. + CD-ROM